Šport: prostor brez meja: Priročnik za vključevanje otrok s posebnimi potrebami v društvene športne dejavnosti in izvajanje vključujoče/inkluzivne športne vadbe - Maver, Nuša (University of Maribor Press, 2025)
Sport: A Space Without Borders. A Manual on the Inclusion of Children with Special Needs in Sports Club Programs and the Implementation of Inclusive Sports Training. The manual for including children with special needs in sports activities and implementing inclusive sports training is intended for teachers, coaches, sports clubs, and organizations that aim to make sports accessible to a wider population of young people. It offers a comprehensive overview of inclusive sports training and includes strategies, tools, and practical guidelines for adapting physical and sports activities to participants with diverse characteristics and needs. The first part of the manual focuses on the inclusive paradigm, which serves as the foundation for successfully conducting inclusive physical/sports activities. The second part provides guidelines for working with specific groups of children with special needs, along with recommended adaptations during the training process. These adaptations relate to the environment, equipment and tools, content, and methods of delivering the training sessions. The purpose of the manual is to empower coaches and physical education teachers to effectively implement inclusive sports activities and to contribute to the increase in providers of segregated, integrated, and inclusive sports training.